Histopathology of Infectious Colitis - Christina M. Surawicz (Canadian Journal of Gastroenterology)
Histopathology can play an important role in diagnosing infictious colitis for several reasons. First, colonic mucosal biopsy can often reliably differentiate acute self limited colitis (ASLC). or infectious type colitis, from idiopathic inflammatory bowel disease (IBD). In ASLC, crypt architecture is normal and the inflammatory infiltrate in the lamina propria predominantly acute, ie, polymorphonuclear cells. In IBD, in contrast, crypt architecture is often abnormal nd the inflammatory infiltrate in the lamina propria in both acute and chronic, ie, polymorphonuclear cells, plasma cells ,and lymphocyte are present in increased numbers. Second, biopsy may give a clue to the specific infection. Biopsy may reveal the presence of specific parasites such as Entamoeba histolytica, cryptosporidia or schistosomiasis. Viral inclusions are seen when cytomegalovirus or herpes simplex type II virus infect the colon. Granulomas usually indicate Crohn's disease but can he seen with infections due to Chlamydia trachomatis, Treponema pallidum and Mycobacterium tuberculosis. Both chlamydial and syphilitic proctitis are rare and usually seen in homosexually active men. Finally, pseudomembranes, when present, suggest pseudomembranous colitis due to an overgrowth of toxigenic Clostridium difficile. In summary, mucosal biopsy is helpful in differentiating ASLC from IBD in most cases. Sometimes, it provides a clue to the specific infection.